Implementasi Program Posyandu dalam Penurunan Angka Stunting di Desa Manggopoh - Bismil Selvia; Solfema Solfema; Lili Dasa Putri (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The condition of stunting in rural areas reflects the challenges faced by many rural areas in Indonesia. Various complex factors such as inadequate nutrition, limited access to health services, poor sanitation, and low levels of public awareness about the importance of nutrition during growth. This type of research is qualitative descriptive research. The research subjects were Posyandu cadres in rural areas and the community (mothers of toddlers). This research uses narratives or words to discuss problems, the aim is to describe and explain the situation or phenomenon regarding the implementation of the posyandu program in reducing stunting rates in rural areas. This research uses primary data obtained from direct sources surveyed and secondary data obtained from books, records and related documents from Village Posyandu, Puskesmas and other appropriate sources. Data collection techniques include: (a) Observation, which uses a type of passive observation carried out by researchers when visiting research locations to observe and collect data, (b) Interview, which is a method used by asking questions to informants who are considered interested. understand the focus of the research. The stunting prevention program includes (1) providing additional nutrition (PMT); (2) giving vitamin A in addition to breast milk; (3) giving blood supplement tablets (TTD) to pregnant women; (4) providing complete basic vaccinations; (5) monitor the baby's development; (6) environmental cleanliness.